A Comparative Study of Competencies of Future Management Accounting Professionals in Lithuania and Latvia Using a Multi-Criteria Model - Tamulevičienė, Daiva; Vareikaitė, Aistė; Būmane, Inga (Buhalterinės apskaitos teorija ir praktika, 2024)
Management accountants' high level of competence is essential for every company, as they manage a large amount of financial and non-financial information based on which managers make appropriate and timely decisions. However, the question arises as to whether the knowledge, skills and values of a management accountant, as referred to in the academic literature, are equally important in assessing such professionals' competence. Some elements are likely more important than others. This paper aims to identify the competencies required for a modern management accountant and quantify the importance of each competence element using a multi-criteria assessment approach. Such a multi-criteria model could be helpful for companies looking for management accountants to define the required level of competence, for management accountants and accounting students to assess their competencies and, if necessary, to improve the missing competencies. The study identified six competencies needed for a modern management accountant, among which the essential competencies identified by the experts were analytical skills and knowledge of corporate finance. Based on the experts' estimates, two multi-criteria models for assessing the competencies of a modern management accountant were developed and applied to evaluate the level of management accounting competencies of Lithuanian and Latvian accounting students.
Keywords: management accounting; competencies; multi-criteria model; Lithuania; Latvia